Strategi Kebijakan Pemerintah Kota Bandar Lampung dalam ‎Penguatan Urban Farming dan Ketahanan Pangan - Eliza Eliza (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Urban food security in Bandar Lampung faces increasingly complex challenges due to households’ high dependence on market supplies, food price fluctuations, distribution disruptions, an increasing urban population, and the presence of food-insecure priority areas. This study aims to analyze the Bandar Lampung City Government’s policy strategies for strengthening urban farming as an instrument of urban food security, identify priority issues, evaluate policy alternatives, and formulate integrated policy recommendations. This study employs a qualitative-descriptive approach based on policy analysis, utilizing secondary data from the Central Statistics Agency (BPS), the Food Security and Vulnerability Atlas, local government documents, relevant regulations, and pertinent scientific literature. The analysis was conducted through problem identification, prioritization using the urgency, seriousness, and growth method, the avoid–shift–improve strategic framework, and an evaluation of four policy alternatives based on economic, social, political, and technical aspects. The research results indicate that the main issues regarding food security in Bandar Lampung are households’ high dependence on markets for fresh produce, the suboptimal development of backyard and community-based urban farming, and the weak integration of urban farming with the city’s food security policies. Of the four alternatives analyzed, the integration of urban farming.